Exploring Selfhood In Arthur Miller's ''The Crucible: Uncovering the Search for Selfhood in Arthur Miller's 'The Crucible' (Journal of Advances and Scholarly Researches in Allied Education, 2011)
The purpose of the present analysis of“The Crucible” is to study the action of the play in terms of the implication of Exploration for Selfhood of the characters involved by scrutinizing the various dilemmas into which the characters find themselves. The self of an individual becomes foregrounded in the momentof crisis, which involves emotional, moral and social predicaments. Such situations lead theindividual to enter into aprocessof covert introspection, which leads to certain decisions resulting in an overt action. Thus, the study of the actions of characters in a play can effectively lead to an understanding of the nature of their ‘self’. By studying the play from the perspective mentioned earlier, the researcher hopesto uncover ahidden search for Selfhood in the play.